Molecular-weight and cooling-rate dependence of polymer thermodynamics in molecular dynamics simulation - Wang, Yao-Chun; Zhang, Jun-Fu; Chiu, Min-Hsueh; Li, Jia-Han; Jui, Chia-Yung; Yang, Te-Hsun; Lee, Wen-Jay (Polymer journal, 2021)
Molecular dynamics (MD) simulations are conducted to systematically benchmark the effects of molecular weight, chain number, and cooling rate on the glass transition temperature (Tg) and coefficient of thermal expansion (CTE) of poly(ethylene oxide) (PEO). Hyperbolic regression as an objective identified method is used to extract Tg and CTE. The results show that for a cooling rate higher than 5 × 10 13 K/min, Tg and CTE are both strongly affected by rapid quenching. For a cooling rate lower than 5 × 10 13 K/min, Tg and CTE in the high-temperature domain still slightly depend on the cooling rate. Eventually, to eliminate the finite size effect of the model, a threshold molecular weight of 11,240 g/mol should be satisfied in the system. In addition, the chain number must be more than 10, at least for an oligomer system (50 monomers). This study comprehensively reveal the critical parameters of poly(ethylene oxide) (PEO) in the MD simulation that causes the numerical effect on polymer simulation and the variation of thermodynamics property. The threshold value of total molecular weight of 11,240 g/mol must be satisfied, which leads the polymer that exhibits its steady state bulk properties. For the oligomer system (Mw < 2248 g/mol per chain (50 monomers)), the total chain number must be more than 10 at least. The cooling rate must be lower than 5 × 10 13 K/min for the structural equilibrium.